2011
DOI: 10.1007/s10641-011-9814-2
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of fish species in streams: relationships between assemblage attributes and trophic and environmental variables

Abstract: Diet overlap and niche breadth are wellknown species traits from trophic ecology that can assist in explaining how species interact and coexist as well as the ecological mechanisms that influence biodiversity. In the present study, we analyzed the relationships between these trophic variables and indicators of resource availability with some attributes of fish assemblages (species richness, Shannon diversity index, evenness, density and individual body size). The physical and chemical characteristics of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…The present study reveals that food resource partitioning between salmon and bullhead can vary within a river system, between sites at relatively short distances from each other, and between seasons at a given site, with resource partitioning being strongly dependent on prey diversity at different sites. Studies on other species have given indication that high prey diversity may enhance food resource partitioning (see, e.g., Hillebrand & Shurin, ; Jiang et al., ; Martin & Garnett, ; Zapata et al., ) and that competition for food is high when prey diversity is low (Barili et al., ; Hillebrand & Shurin, ; Targett, ). Our study corroborates these findings and supports the notion that high prey diversity may promote consumer coexistence through food resource partitioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study reveals that food resource partitioning between salmon and bullhead can vary within a river system, between sites at relatively short distances from each other, and between seasons at a given site, with resource partitioning being strongly dependent on prey diversity at different sites. Studies on other species have given indication that high prey diversity may enhance food resource partitioning (see, e.g., Hillebrand & Shurin, ; Jiang et al., ; Martin & Garnett, ; Zapata et al., ) and that competition for food is high when prey diversity is low (Barili et al., ; Hillebrand & Shurin, ; Targett, ). Our study corroborates these findings and supports the notion that high prey diversity may promote consumer coexistence through food resource partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barili et al. () reported that high fish abundance and diversity can promote trophic specialization in sympatric species, thereby enhancing food resource partitioning, and density‐dependent foraging behavior may occur when resources are limited (Sánchez‐Hernández & Cobo, ). Noteworthy, our interferences regarding the influence of density dependence on the competition for food should be taken with some caution because our analyses included the overall fish density regardless of fish size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent models have assumed that communities are randomly assembled (Hubbell 2001); however, evidence from freshwater fish communities in tropical floodplains highlights the importance in their organization of factors such as biotic interactions (Winemiller 1996;de Mérona & de Mérona 2004;Barili et al 2011), species-habitat associations (Peres-Neto 2004;Rodrigues et al 2013) and environmental filtering (Rondón Suárez et al 2004;de Melo et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The guild structure does not only incorporate food type (prey items), but also foraging habits and foraging habitats. The guild structure of an ecosystem is often more stable in time than its species composition, because the species within a guild can take over each other's functional role, following slight fluctuations in environmental conditions (Aarts & Nienhuis, 2003;Barili et al, 2011).…”
Section: Discussionmentioning
confidence: 99%